Risk Mitigation Design Based on Halal Standards and Environmental Sustainability Aspects using SCOR DS Model and HOR Method - Maulina Halin; Yandra Rahadian Perdana; Dwi Agustina Kurniawati (Jurnal INTECH Teknik Industri Universitas Serang Raya, 2025)
This study aims to identify, analyze, and mitigate risks in the broiler chicken supply chain at PT. XYZ by considering halal standards and environmental sustainability. Risk mapping according to the supply chain process was carried out using the Supply Chain Operation Reference Digital Standard (SCOR DS) approach model;  on the other hand, the House of Risk (HOR) method, stage 1 was used to determine the priority of risk agents and stage 2 was used to formulate effective mitigation strategies. The analysis results show 17 priority risk agents that significantly affect 80% of risk events, including the number of chickens slaughtered, poor administration, unpleasant odors, irregular working hours, delivery disruptions, and unhygienic equipment. The proposed mitigation strategies include scheduling, seasonal recruitment, warehouse management systems, waste management, routine sanitation, administrative digitization, loading and unloading supervision, weather monitoring, alternative delivery routes, and traceability implementation. The implementation of this strategy is expected to minimize the impact of risks, maintain halal integrity, support environmental sustainability, and increase the company's competitiveness.